Papermaking method using a retention improvement system

JP7634831B2Active Publication Date: 2025-02-25HYMO CORPORATION
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021044192
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-18
Publication Date
2025-02-25
Estimated Expiration
2041-03-18

AI Technical Summary

Benefits of technology

【0006】 抄紙前の製紙原料に、本発明におけるアニオン性水溶性高分子を添加後、カチオン性凝結剤を添加することで添加率を上げても濾水性や搾水性の低下を招くことなく歩留効果を発揮し、生産性の向上や紙品質の向上を達成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634831000001
    Figure 0007634831000001
  • Figure 0007634831000002
    Figure 0007634831000002
  • Figure 0007634831000003
    Figure 0007634831000003
Patent Text Reader

Abstract

To provide a papermaking method of a paper raw material using a yield improving system in a papermaking step, that achieves yield improvement of the paper raw material without lowering a water filtering property and a water drainage property even if an addition ratio is raised.SOLUTION: A papermaking method includes adding to a paper raw material an anionic water-soluble coagulant having a specific composition and an inherent viscosity measured at 0.5 mass% thereof at 25°C in a 4 mass% salt aqueous solution is 10-30 dl / g, and then adding a cationic coagulant, the papermaking method being applied to be able to achieve yield improvement without lowering a water-filtering property. One or more kinds selected from an organic coagulant and / or an inorganic coagulant are added as the cationic coagulant.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a papermaking method for improving the retention and drainage of papermaking raw materials by using a retention aid in the papermaking process, and more particularly to a papermaking method for improving the retention and drainage of papermaking raw materials on a wire by a retention system using a retention aid in the papermaking process. [Background technology]

[0002] In the papermaking process for coating base paper, PPC paper, wood-free paper, paperboard, newsprint, etc., retention aids are used to improve the retention rate on the wire of raw pulp, fine fibers, fillers, papermaking chemicals, etc., or drainage aids (or yield and drainage aids) that emphasize the function of improving drainage as well as retention are used. Generally, polyacrylamide (PAM) polymers are widely used as retention aids, but due to the diversification of papermaking conditions in recent years, effective retention aids and retention systems vary. As a retention system using two or more liquids, various systems have been devised that take into consideration the ion balance, mainly using PAM-based polymers, in accordance with the papermaking conditions and the properties of the papermaking raw materials. Generally, a system is used in which a cationic polymer is first added to the papermaking raw materials before papermaking. For example, a prescription in which a cationic or amphoteric PAM is added, followed by an anionic PAM (Reference 1), a prescription in which a cationic polymer is added, followed by bentonite, an anionic inorganic substance (Reference 2), a prescription in which a cationic or amphoteric PAM retention aid is added, followed by a water-soluble polymer with a lower molecular weight than the retention aid (Reference 3), and the like are in practical use. In addition to the general recipe of adding a cationic polymer first, a recipe of adding an amphoteric or anionic polymer first and then adding a cationic polymer has also been proposed. For example, a recipe of adding a water-soluble branched anionic polymer and then adding a cationic or amphoteric polymer (Patent Document 4) and a recipe of adding an anionic polymer and then further adding an anionic polymer (Patent Document 5) have been disclosed. However, in these recipes, if the addition rate is increased to improve the retention rate of the papermaking raw material on the wire, excessive water is taken into the formed flocs, which may result in reduced freeness and water squeezing, or the paper quality may deteriorate, resulting in reduced productivity. Therefore, there is a demand for a retention improvement system that can improve the freeness improvement effect as well as the retention improvement effect on the wire part of the papermaking raw material in order to increase production efficiency.

[0003] [Patent Document 1] JP 2001-254290 A [Patent Document 2] Japanese Unexamined Patent Publication No. 62-191598 [Patent Document 3] JP 2009-280925 A [Patent Document 4] Special Publication No. 2010-518268 [Patent Document 5] JP 2010-77546 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention relates to a method for making paper from raw paper using a retention aid in the papermaking process, and has an object to provide a papermaking method that can improve the retention of raw paper on the wire without deteriorating freeness or texture even when the addition rate is increased. [Means for solving the problem]

[0005] As a result of intensive research to solve the above problems, it was discovered that it is possible to improve the retention and drainage of papermaking raw materials by adding an anionic water-soluble polymer having a specific composition and physical properties to the papermaking raw materials before papermaking, and then adding a cationic coagulant. Effect of the Invention

[0006] By adding the anionic water-soluble polymer of the present invention to the papermaking raw material before papermaking, and then adding a cationic coagulant, a retention effect can be achieved without causing a decrease in drainage or water squeezing, even when the addition rate is increased, and improvement in productivity and paper quality can be achieved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The anionic water-soluble polymer in the present invention is produced by polymerizing an aqueous monomer mixture solution containing 5 to 80 mol % of a monomer represented by the following general formula (1) and 20 to 95 mol % of a nonionic monomer. TIFF0007634831000001.tif2660 General formula (1) R 1 is hydrogen, methyl or carboxymethyl, and Q is SO 3 ― , C 6 H 4 SO 3 ― , CONHC(CH 3 ) 2 CH 2 SO 3 ― ,a Rui is COO ― , R 2 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen atom or a cation.

[0008] The anionic monomer used in producing the anionic water-soluble polymer of the present invention, i.e., the monomer represented by the general formula (1), is in the range of 5 to 80 mol %. If it is less than 5 mol %, a large flocculation effect due to the anionic group of the anionic water-soluble polymer cannot be obtained, and if it is more than 80 mol %, it becomes difficult to obtain a high molecular weight polymer. The range of 10 to 60 mol % is preferable.

[0009] The anionic monomer represented by the general formula (1) is, for example, vinyl sulfonic acid, vinylbenzene sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methacrylic acid, acrylic acid, itaconic acid, maleic acid, etc. ,a or their salts. Two or more of these may be used in combination.

[0010] The nonionic monomer used in the present invention includes (meth)acrylamide, N,N'-dimethylacrylamide, acrylonitrile, (meth)acrylate-2-hydroxyethyl, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, acryloylmorpholine, etc. Two or more of these may be combined. The molar amount of the nonionic monomer is 20 to 95 mol%, preferably 40 to 90 mol%.

[0011] When producing the anionic water-soluble polymer of the present invention, a cationic monomer can be used within a range that does not impair the effect. The amount of the cationic monomer used is in the range of 0 to less than 10 mol %, and if it is 10 mol % or more, the function as an anionic water-soluble polymer is reduced. It is preferably less than 5 mol %.

[0012] When using cationic monomers in the present invention, the following are available. That is, quaternized products of methyl chloride or benzyl chloride such as dimethylaminoethyl (meth)acrylate and dimethylaminopropyl (meth)acrylamide. Examples include (meth)acryloyloxyethyl trimethylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl trimethylammonium chloride, (meth)acryloylaminopropyl trimethylammonium chloride, (meth)acryloyloxyethyl dimethylbenzylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl dimethylbenzylammonium chloride, and (meth)acryloylaminopropyl dimethylbenzylammonium chloride. Two or more of these can also be combined.

[0013] The product form of the anionic water-soluble polymer in the present invention is not particularly limited, and can be produced by a known method. The anionic water-soluble polymer in the present invention can be produced by copolymerizing a monomer mixture containing an anionic monomer and a nonionic monomer. After preparing an aqueous solution of these monomers, the polymerization is carried out by, for example, aqueous solution polymerization, water-in-oil emulsion polymerization, water-in-oil dispersion polymerization, dispersion polymerization in salt water, etc., and then any product form such as an aqueous solution, water-in-oil emulsion, dispersion in salt water, or powder can be used. Among these polymerization methods, water-in-oil emulsion polymerization or dispersion polymerization in salt water is preferred, as it is easy to produce a polymer with a high molecular weight.

[0014] The water-in-oil emulsion can be appropriately produced according to the method described in JP-A-55-137147, JP-A-59-130397, JP-A-10-140496, JP-A-2011-99076, etc. That is, a monomer mixture containing an anionic monomer and a nonionic monomer is mixed with water, an oily substance consisting of a hydrocarbon immiscible with water, and at least one surfactant having an effective amount and HLB for forming a water-in-oil emulsion, and the mixture is stirred vigorously to form a water-in-oil emulsion, followed by polymerization.

[0015] When the anionic water-soluble polymer of the present invention is prepared by dispersion polymerization in salt water, it can be appropriately produced according to JP-A-62-20511, JP-A-10-212320, JP-A-2004-231822, etc. That is, the polymer is produced by dispersing a mixture of anionic monomers and nonionic monomers in a salt water solution in the presence of a polymer dispersant soluble in the salt water solution.

[0016] In the anionic water-soluble polymer of the present invention, a crosslinkable monomer such as N,N'-methylenebis(meth)acrylamide or triallylamine may be used as a structural modifier during or after polymerization. When a crosslinkable monomer is used, the amount of the crosslinkable monomer is preferably 10 ppm or less based on the total amount of monomers. The anionic water-soluble polymer in the present invention is preferably a straight-chain polymer. It is preferable that it is produced in the absence of a crosslinkable monomer and has substantially no branched or crosslinked structure. This is because the straight-chain polymer tends to have a higher reactivity with the cationic coagulant added to the second liquid, improving the performance of the retention improvement system in the present invention.

[0017] The anionic water-soluble polymer in the present invention needs a high molecular weight to obtain a high coagulation force. The molecular weight is expressed in terms of intrinsic viscosity, and the intrinsic viscosity of the water-soluble polymer in a 4 mass% saline solution at 0.5 mass% measured at 25°C is 10 to 30 dl / g, preferably 15 to 30 dl / g, and more preferably 18 to 30 dl / g. If the intrinsic viscosity is lower than 10 dl / g, the effect of improving the retention rate is significantly reduced, and if it is higher than 30 dl / g, the quality of the paper, especially the texture, tends to deteriorate, which is not preferable. The weight average molecular weight measured by the intrinsic viscosity method is preferably within the range of 10 to 30 million.

[0018] In the present invention, after the anionic water-soluble polymer is added as the first liquid, a cationic coagulant is added as the second liquid. As the cationic coagulant, one or more selected from organic coagulants and inorganic coagulants are used. As the organic coagulant, dialkylaminoalkyl (meth)acrylate polymers, vinylamine polymers, ethyleneimine polymers, condensed amine polymers, amidine polymers, diallylamine polymers, dicyandiamide polymers, etc. are listed. Among these, vinylamine polymers and ethyleneimine polymers are preferred. As the inorganic coagulant, polyaluminum chloride, aluminum sulfate, aluminum chloride, ferric chloride, ferric sulfate, polyferric sulfate, etc. are listed. Among these, polyaluminum chloride (PAC) or aluminum sulfate (aluminum sulfate) is preferred. In addition, the organic coagulant and the inorganic coagulant may be used in combination.

[0019] Tertiary amino group-containing cationic monomers that are used as constituent units of the dialkylaminoalkyl (meth)acrylate polymer of the organic coagulant include dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylamide, diethylaminopropyl (meth)acrylamide, and salts thereof. In addition, quaternary ammonium base-containing cationic monomers that are monohalogenated versions of the tertiary amino group-containing cationic monomers include (meth)acryloyloxyethyl trimethyl ammonium chloride, (meth)acryloyloxyethyl dimethyl benzyl ammonium chloride, (meth)acryloylaminopropyl trimethyl ammonium chloride, (meth)acryloylaminopropyl dimethyl benzyl ammonium chloride, (meth)acryloyloxy 2-hydroxypropyl trimethyl ammonium chloride, and the like. Polymers of these cationic monomers alone, polymers of two or more cationic monomers, and copolymers of cationic monomers and nonionic monomers may also be used. Examples of nonionic monomers include (meth)acrylamide, N,N'-dimethylacrylamide, vinyl acetate, acrylonitrile, methyl acrylate, 2-hydroxyethyl (meth)acrylate, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, acryloylmorpholine, etc., and copolymers of one or more of these with cationic monomers can be used. The weight average molecular weight of the dialkylaminoalkyl (meth)acrylate polymer is preferably in the range of 10,000 to 3,000,000.

[0020] Examples of vinylamine polymers include polyvinylamines formed from acid- or alkali-modified polymers having N-vinylcarboxylic acid amide, N-vinylformamide, N-vinylacetamide, etc. as essential monomers, and copolymers of vinylamine units and one or more selected from cationic monomers and nonionic monomers used in producing the dialkylaminoalkyl(meth)acrylate polymers. The weight-average molecular weight is preferably in the range of 10,000 to 3,000,000.

[0021] Examples of ethyleneimine-based polymers include polyethyleneimine and polyethyleneimine modifications, etc. The weight-average molecular weight is preferably in the range of 10,000 to 3,000,000.

[0022] Examples of the condensation amine polymer include condensates of epichlorohydrin with monomethylamine, dimethylamine, monoethylamine, diethylamine, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, etc., or condensates of the above aliphatic amine / epichlorohydrin condensates with ethylenediamine, diethylenetriamine, triethylenetetramine, or hexamethylenediamine. The weight average molecular weight is preferably in the range of 1,000 to 100,000.

[0023] The amidine polymer can be synthesized by hydrolysis of a copolymer of N-vinyl carboxylic acid amide and (meth)acrylonitrile with an acid. Examples of N-vinyl carboxylic acid as a monomer include N-vinyl formamide and N-vinyl acetamide. The acid used is preferably an inorganic or organic strong acid, such as hydrochloric acid, nitric acid, or p-toluenesulfonic acid. Acrylonitrile is the most common vinyl nitrile to be copolymerized. The molar percentage of amidine groups in the molecule after hydrolysis is 5 to 100 molar percent, preferably 10 to 100 molar percent, and most preferably 20 to 100 molar percent. The nonionic structural unit is an unhydrolyzed carboxylic acid amide group and an unreacted nitrile group, and the molar percentage is 0 to 95 molar percent, preferably 0 to 90 molar percent, and most preferably 0 to 80 molar percent. The weight average molecular weight is preferably in the range of 10,000 to 4,000,000.

[0024] Examples of monomers used for the diallylamine polymer include allylamine, diallylmethylamine and their salts, diallyldimethylammonium chloride, etc. Polymerized monomers of these alone, and copolymerized monomers of these monomers with one or more selected from cationic monomers and nonionic monomers used in producing dialkylaminoalkyl(meth)acrylate polymers can also be used. The weight average molecular weight is preferably in the range of 10,000 to 4,000,000.

[0025] Dicyandiamide polymers include water-soluble dicyandiamide-formaldehyde condensation products and dicyandiamide-formaldehyde-ammonium chloride condensation products. Basically, they are products of condensation of dicyandiamide with formaldehyde in the presence of an acid or its ammonium salt. The weight-average molecular weight is preferably in the range of 10,000 to 500,000.

[0026] The cationic equivalent value of these organic coagulants at pH 7 is preferably 3.0 meq / g or more. The preferred range is 3.0 to 22.0 meq / g. The preferred range is 1 to 10 mPa s for the 4 mass% saline solution viscosity (SLV) measured with a rotational viscometer at 25°C when the organic coagulant is completely dissolved so that the polymer concentration is 0.5 mass%. A B-type viscometer such as Tokyo Keiki's B8M is used, and the values ​​are measured at 60 rpm with a No. 1 rotor.

[0027] The anionic water-soluble polymer and cationic coagulant of the present invention are added to the papermaking raw material before papermaking. Usually, in the papermaking process, the papermaking raw material transferred from the upstream with a pulp dry solids concentration of 2.0% by mass or more is diluted with white water or fresh water just before the papermaking machine to a papermaking raw material with a pulp dry solids concentration of less than 2.0% by mass. Generally, it is diluted to 0.5 to 1.5% by mass, and these are called inlet raw materials or headbox raw materials. A retention aid is added to these raw materials (hereinafter referred to as inlet raw materials) and paper is made. The retention improvement system of the present invention is also applied to the inlet raw materials.

[0028] The anionic water-soluble polymer and cationic coagulant of the present invention can be added in the papermaking process before or after a fan pump or before or after a screen, which is a shearing process. As long as the order of addition is such that the cationic coagulant is added after the anionic water-soluble polymer of the present invention, the present invention can be applied to any of these addition locations.

[0029] The anionic water-soluble polymer in the present invention has a certain high molecular weight, and forms relatively large flocs by coagulation with cationic groups of papermaking chemicals such as cationic starch and paper strength agents. The formed flocs are then gradually broken down into smaller flocs during transportation and shearing. Fine flocs are formed by the coagulation of unreacted anionic groups in the anionic water-soluble polymer in the flocs and the anionic substances and cationic coagulants in the suspension of papermaking raw materials, and the flocs are made into paper in the wire part. This mechanism is believed to improve the yield without introducing much moisture into the flocs.

[0030] The types of paper for which the anionic water-soluble polymer and cationic coagulant of the present invention are used include newsprint, fine printing paper, medium printing paper, gravure printing paper, PPC paper, coated base paper, lightly coated paper, packaging paper, liner and core base paper board, etc. The anionic water-soluble polymer of the present invention is effective for papermaking raw materials with a relatively low anion content, i.e., cationic demand. Specifically, the cationic demand is 0.03 meq / L or less, and is preferably 0.02 meq / L or less. The anionic water-soluble polymer of the present invention is also effective even if the papermaking raw material exhibits cationicity (=anionic demand). It is effective when applied to a papermaking system with a high addition rate of cationic or amphoteric starch, synthetic strength agents, or aluminum sulfate. The cationic demand is expressed as a value (meq / L) measured by a commercially available particle charge meter (such as PCD-05 model by Mutec Co., Ltd.) for the filtrate from Whatman No. 41 filter paper.

[0031] The anionic water-soluble polymer and cationic coagulant in the present invention are used by diluting and dissolving in water to 0.01 to 1.0% by mass. The water to be dissolved may be distilled water, ion-exchanged water, tap water, industrial water, etc. A mixture of these may also be used. The diluted solution may also be further diluted a second time or a third time. The addition rate of the anionic water-soluble polymer is in the range of 10 to 1000 ppm (polymer pure content) relative to the solid content concentration of the paper stock. The addition rate of the cationic coagulant is in the range of 10 to 5000 ppm (solid content equivalent) relative to the solid content concentration of the paper stock.

[0032] The anionic water-soluble polymer and cationic coagulant of the present invention can be used in combination with paper strength agents, sizing agents, and other papermaking chemicals. In addition, they may also be used in combination with other retention aids, but it is preferable to use only the retention aid system of the present invention, as this is more advantageous. EXAMPLES

[0033] The papermaking method of the papermaking raw material using the anionic water-soluble polymer and the cationic coagulant of the present invention will be specifically described below, but the present invention is not limited to the following examples.

[0034] (Anionic water-soluble polymer sample) The anionic water-soluble polymer samples A and B of the present invention were prepared by the usual methods of water-in-oil emulsion polymerization and dispersion polymerization in salt water, respectively. Anionic water-soluble polymer sample C outside the scope of the present invention was prepared by the usual method of water-in-oil emulsion polymerization. The compositions and physical properties of these are shown in Table 1.

[0035] (Table 1) TIFF0007634831000002.tif2490Monomer composition; AAC: acrylic acid, AAM: acrylamide Product form: E: Water-in-oil emulsion, D: Dispersion polymer in salt water Intrinsic viscosity: the intrinsic viscosity of a water-soluble polymer in a 4% by mass saline solution at 0.5% by mass measured at 25°C. Viscosity of 0.2% by mass aqueous solution: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in water to a concentration of 0.2% by mass.

[0036] (Cationic retention aid sample) As comparative samples, commercially available cationic retention aids D and E were prepared. Their compositions and physical properties are shown in Table 2.

[0037] (Table 2) TIFF0007634831000003.tif2291 Product form: E: Water-in-oil emulsion, D: Dispersion polymerized liquid in salt water Intrinsic viscosity: the intrinsic viscosity of a water-soluble polymer in a 4% by mass saline solution at 0.5% by mass measured at 25°C.

[0038] (Cationic coagulant sample) As the cationic coagulant in the present invention, organic coagulant samples were prepared or manufactured from commercially available products. Their compositions and physical properties are shown in Table 3. In addition, as inorganic coagulants, commercially available products PAC (polyaluminum chloride, alumina concentration 10 mass%, the stock solution used as 100 mass% solids) and aluminum sulfate (aluminum sulfate, alumina concentration 8 mass%, the stock solution used as 100 mass% solids) were prepared.

[0039] (Table 3) TIFF0007634831000004.tif5491Product form;AQ:Water-soluble polymer liquid Viscosity of 0.5% by mass salt solution: Viscosity (mPa s) measured at 25°C when the polymer is dissolved in 4% by mass salt solution to a concentration of 0.5% by mass.

[0040] (Test Example 1, Drainage Performance Evaluation Test) (Examples 1 to 16) Drainage performance was evaluated using a dynamic drainage analyzer (DDA, Matsubo). LBKP prepared to a beating degree of 350 mL was diluted with clean water, light calcium carbonate was added, and the pH was adjusted to prepare inlet stock for testing. The physical properties of the prepared inlet stock were solids concentration of 13215 ppm, light calcium carbonate and other ash solids concentration of 2771 ppm (relative to stock solids), pH 8.5, and electrical conductivity 36.1 mS / m. The turbidity of the Whatman No. 41 filter paper filtrate of the prepared inlet stock was 299 NTU (using HACH's 2100P model), and the cation demand was 0.011 meq / L (using Mutec's PCD-05 model). A predetermined amount of the prepared inlet stock was put into a DDA stirring tank with a 62 mesh wire at the bottom. After stirring for 5 seconds at 1000 rpm, 0.5% by mass of aluminum sulfate was added (relative to the stock solids), stirring for 20 seconds at 1000 rpm, 0.3% by mass of commercially available cationized starch was added (relative to the stock solids), stirring for 20 seconds at 1000 rpm, 0.1% by mass of aqueous solution of sample A in Table 1 was added as the first liquid at 300 ppm relative to the stock solids (pure polymer content), stirring for 20 seconds at 1000 rpm (assuming addition at the screen inlet), 100% by mass of aqueous solution of sample 1 in Table 3 was added as the second liquid at 100 ppm (pure polymer content), stirring for 10 seconds at 1000 rpm (assuming addition at the screen outlet), and the stock was sucked under a reduced pressure of 300 mBar, and the drainage time and sheet moisture content were measured when a sheet was formed on the wire. This is Example 1. In addition, similar tests were carried out under similar conditions using the same prepared inlet paper stocks and inorganic coagulant samples shown in Tables 1 to 3 (Examples 2 to 16). The results are shown in Table 4.

[0041] (Test Example 1, Drainage Performance Evaluation Test) (Comparative Examples 1 to 14) Using the same prepared inlet paper stock and inorganic coagulant samples as in Example 1, similar tests were carried out under the same conditions as in Example 1, but with different samples and addition orders. The results are shown in Table 4.

[0042] (Table 4) TIFF0007634831000005.tif10191

[0043] In the examples in which a cationic coagulant was added after the addition of the anionic water-soluble polymer of the present invention, the drainage time was shortened and the sheet moisture content was lower than in the comparative examples. In the comparative examples in which the addition method was different from that of the present invention, no results were obtained showing both a shortened drainage time and a lower sheet moisture content. The addition method of the present invention confirmed the drainage performance and water squeezing performance.

[0044] (Test Example 2, Yield Measurement Test) (Examples 17 to 30) In the retention rate measurement test, a Britt type dynamic jar tester (using 30 mesh wire) was used. A certain amount of the same inlet stock as in Example 1 was collected, 0.5% by mass of aluminum sulfate was added (relative to the stock solids), and the stirring speed was 1000 rpm for 20 seconds. 0.3% by mass of cationized starch was added (relative to the stock solids), and the stirring speed was 1000 rpm for 20 seconds. As the first liquid, 300 ppm of a 0.1% by mass aqueous solution of sample A in Table 1 was added to the stock solids (pure polymer content), and after stirring for 20 seconds at a stirring speed of 1000 rpm (assuming addition to the screen inlet), and as the second liquid, 100 ppm of a 0.1% by mass aqueous solution of sample 1 in Table 3 was added (pure polymer content), and after stirring for 10 seconds at a stirring speed of 1000 rpm (assuming addition to the screen outlet), the filtrate was collected for a certain period of time, filtered with ADVANTEC No. 2 filter paper, and the SS was measured to determine the total retention rate. The filter paper was incinerated at 525 ° C for 2 hours, and the ash retention rate was measured. This is Example 17. In addition, similar tests were carried out under similar conditions using the same prepared inlet paper stock, Tables 1 and 3, or inorganic coagulant samples (Examples 18 to 30). The results are shown in Table 5.

[0045] (Test Example 2. Yield Measurement Test) (Comparative Examples 15 to 22) Using the same prepared inlet paper stock as in Example 1, and the inorganic coagulant samples in Tables 1 and 3, similar tests were carried out under the same conditions as in Example 1, but with different samples and addition orders. The results are shown in Table 5.

[0046] (Table 5) TIFF0007634831000006.tif8791

[0047] The addition method of the present invention resulted in maintaining or improving the yield rate compared to the comparative examples. This means that by applying the addition method of the present invention, the retention effect is equal to or greater than that of the comparative examples, and the freeness and squeezing can be improved, and the addition rate of the system for further improving the retention rate can be increased. On the other hand, in a comparison between comparative examples 15 and 16, by changing the addition of sample A from the screen inlet to the screen outlet, the collapse of the formed flocs due to the stirring shear of the screen is suppressed, and the yield rate is improved, but from the results of comparative example 2 of (Test Example 1. Drainage Performance Evaluation Test), excessive water is taken into the flocs, and the freeness and squeezing are greatly reduced. In addition, adding a high molecular weight polymer to the screen outlet has a large effect on the formation. Therefore, the change to the screen outlet addition or the increase in the addition rate of the anionic water-soluble polymer cannot achieve an improvement in production efficiency. The same can be said about sample B. It was confirmed that the retention effect was relatively low when sample C was added, and even if it was increased, the retention effect of the same level as samples A and B was not obtained, and a certain molecular weight or more was required for the anionic water-soluble polymer.

[0048] (Test Example 3. Drainage Performance Evaluation Test) (Example 31) Drainage performance was evaluated using a dynamic drainage analyzer (DDA, Matsubo). 2% by mass of aluminum sulfate and 0.2% by mass of paper strength agent (both based on stock solids) were added to the prepared inlet stock of the coated base paper raw material obtained from a certain paper company and used for the test. The physical properties of the prepared inlet stock were solids concentration 14811 ppm, light calcium carbonate etc. ash solids concentration 2727 ppm (based on stock solids), pH 7.7, and electrical conductivity 75.1 mS / m. The turbidity of the Whatman No. 41 filter paper filtrate of the prepared inlet stock was 19 NTU (using HACH 2100P model), and the cation demand was 0.025 meq / L (using Mutec PCD-05 model). A predetermined amount of the prepared inlet stock was put into a DDA agitation tank with a 62 mesh wire at the bottom. After stirring for 5 seconds at 1000 rpm, 0.3% by mass of commercially available cationic starch was added (relative to the stock solids), and stirring was continued for 30 seconds at 1000 rpm. As the first liquid, a 0.1% by mass aqueous solution of Sample A in Table 1 was added at 25 ppm (pure polymer content) relative to the stock solids, and stirring was continued for 20 seconds at 1000 rpm (assuming addition to the screen inlet). As the second liquid, a 0.1% by mass aqueous solution of Sample 2 in Table 3 was added at 350 ppm (pure polymer content) relative to the stock solids or PAC was added at 2500 ppm, and stirring was continued for 10 seconds at 1000 rpm (assuming addition to the screen outlet). The stock was sucked under a reduced pressure of 300 mBar, and the drainage time and sheet moisture content were measured when a sheet was formed on the wire. This is Example 31. These results are shown in Table 6.

[0049] (Test Example 3, Drainage Performance Evaluation Test) (Comparative Example 23) Using the same prepared inlet stock as in Example 31, a similar test was carried out under the same conditions as in Example 31, except that 50 ppm (pure polymer content) of commercially available anionic water-soluble polymer sample F [anionic polyacrylamide, anionic equivalent value 4.5 meq / g (pH 7), 0.5 mass% salt solution viscosity 143 mPa s] was added to the first liquid (assuming addition to the screen inlet) based on the stock solids, and 400 ppm of commercially available colloidal silica was added to the second liquid (assuming addition to the screen outlet). The results are shown in Table 6.

[0050] (Test Example 4, Yield Measurement Test) (Example 32) In the retention rate measurement test, a Britt type dynamic jar tester (using 30 mesh wire) was used. A predetermined amount of the same inlet stock as in Example 31 was collected, 0.3% by mass of cationic starch was added (relative to the stock solids), and the stirring speed was 500 rpm for 30 seconds. As the first liquid, a 0.1% by mass aqueous solution of Sample A in Table 1 was added at 25 ppm (pure polymer content) relative to the stock solids, and after stirring at a stirring speed of 500 rpm for 20 seconds (assuming addition to the screen inlet), as the second liquid, a 0.1% by mass aqueous solution of Sample 2 was added at 350 ppm (pure polymer content) relative to the stock solids or PAC 2500 ppm was added, and after stirring at a stirring speed of 500 rpm for 10 seconds (assuming addition to the screen outlet), the filtrate was collected for a certain period of time, filtered with ADVANTEC No. 2 filter paper, and the SS was measured to determine the total retention rate. The filter paper was incinerated at 525 ° C for 2 hours, and the ash retention rate was measured. This is Example 32. These results are shown in Table 6.

[0051] (Test Example 4, Yield Measurement Test) (Comparative Example 24) Using the same inlet stock prepared as in Example 31, a similar test was carried out under the same conditions as in Example 32, except that 50 ppm (pure polymer) of commercially available anionic water-soluble polymer sample F [anionic polyacrylamide, product form: water-in-oil emulsion, anion equivalent: 4.5 meq / g (pH 7), 0.5 mass% salt solution viscosity: 143 mPa s] was added to the first liquid (assuming addition to the screen inlet) based on the stock solids, and 400 ppm of commercially available colloidal silica was added to the second liquid (assuming addition to the screen outlet). The results are shown in Table 6.

[0052] (Table 6) TIFF0007634831000007.tif2591

[0053] For this papermaking raw material, the anionic PAM + colloidal silica retention improvement system of Comparative Examples 23 and 24 was applied, but it was found that the retention improvement system of the present invention can maintain or improve the yield rate at a lower chemical addition cost than the comparative examples, and can improve drainage and dewatering properties.

Claims

1. A papermaking method comprising the steps of: adding, to a papermaking raw material prior to papermaking in a papermaking process, an anionic water-soluble polymer having, as constituent units, 5 to 80 mol % of one or more selected from vinyl sulfonic acid, vinylbenzenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methacrylic acid, acrylic acid, itaconic acid, maleic acid, or salts thereof, and 20 to 95 mol % of a nonionic monomer, as a monomer represented by the following general formula (1), and having an intrinsic viscosity of 10 to 30 dl / g in a 4 mass % saline solution at 0.5 mass % of the anionic water-soluble polymer measured at 25°C: and then adding a cationic coagulant. General formula (1) R 1 is hydrogen, a methyl group or a carboxymethyl group, and Q is SO 3 ― , C 6 H 4 SO 3 ― , CONHC (CH 3 ) 2 CH 2 SO 3 ― , or COO ― , R 2 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen atom or a cation.

2. 2. The papermaking method according to claim 1, wherein the cationic coagulant is one or more selected from the group consisting of organic coagulants such as dialkylaminoalkyl (meth)acrylate polymers, vinylamine polymers, ethyleneimine polymers, condensation amine polymers, amidine polymers, diallylamine polymers, and dicyandiamide polymers.

3. 2. The papermaking method according to claim 1, wherein the cationic coagulant is one or more selected from inorganic coagulants including polyaluminum chloride, aluminum sulfate, aluminum chloride, ferric chloride, ferric sulfate, and polyferric sulfate.

4. The papermaking method according to claim 2, characterized in that the organic coagulant has a cationic equivalent value at pH 7 of 3.0 to 22.0 meq / g.

5. The papermaking method according to claim 2, characterized in that the viscosity measured at 25°C when the organic coagulant is dissolved in a 4% by mass saline solution so that the polymer concentration is 0.5% by mass is 10 mPa·s or less.

Citation Information

Patent Citations

  • Paper manufacturing method

    JP1994504821A

  • Manufacturing of paper or cardboard

    JP2010518268A

  • Method for reducing pitch by anionic water-soluble polymer

    JP2015021195A

  • Manufacturing method of polymer coagulant

    JP2016093800A

  • Manufacturing method of paper and yield improver kit

    JP2017066581A